Pursuing macroeconomic balance in the CARICOM Region : concepts and application - Thomas, Clive Y. (Univ. of Guyana. Institute of development Studies GeorgetownGY, 1994)
Seeks to draw on recent experiences in pursuing macroeconomic balance, growth and development in the CARICOM Region, in order to raise some conceptual and operational issues of broader significance.